The implementation of ineffective dismissal in people with catastrophic illnesses - Arroyo Terán , Ramiro Sebastián (2025)
The Constitution of the Republic of Ecuador establishes the existence of groups of people that must receive priority attention by remaining within vulnerable groups; however, it includes only a few, since the double vulnerability that certain people face is not taken into account. or groups, as is the case of those who suffer from catastrophic diseases. In this context, a qualitative theoretical study is developed in the methodological framework since a deep theoretical exegetical documentary analysis is carried out and the expansion of the figure of ineffective dismissal is proposed, with the aim of this legal figure being inclusive and including people with diseases, catastrophic events, guaranteeing a more equitable and humane work scenario. Therefore, it is concluded that the standard must be more supportive and inclusive, 3 expanding its scope to protect all those workers who demand priority attention and are in conditions of double vulnerability.